2021
DOI: 10.1002/etc.5155
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Bioavailability of Metals in Fish Population Models

Abstract: Population models are increasingly being used to extrapolate individual-level effects of chemicals, including metals, to population-level effects. For metals, it is also important to take into account their bioavailability to correctly predict metal toxicity in natural waters. However, to our knowledge, no models exist that integrate metal bioavailability into population modeling. Therefore, our main aims were to 1) incorporate the bioavailability of copper (Cu) and zinc (Zn) into an individual-based model (IB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Water chemistry was not reported for the population experiment used in our study for validation (Janssen, 1992) and important parameters such as dissolved organic carbon are unknown. For the aims of the present study, bioavailability modeling of metals was not required but the possibility of bioavailability correction of metal toxicity in population models has been demonstrated for rainbow trout (Janssen et al, 2021). Tools specific to metal risk assessment can thus be integrated in ecological models and enhance the applications of ecological models for metal risk assessment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Water chemistry was not reported for the population experiment used in our study for validation (Janssen, 1992) and important parameters such as dissolved organic carbon are unknown. For the aims of the present study, bioavailability modeling of metals was not required but the possibility of bioavailability correction of metal toxicity in population models has been demonstrated for rainbow trout (Janssen et al, 2021). Tools specific to metal risk assessment can thus be integrated in ecological models and enhance the applications of ecological models for metal risk assessment.…”
Section: Resultsmentioning
confidence: 99%
“…Ecological modeling, and population modeling in particular, is an alternative to this approach that utilizes the available toxicity data to allow a mechanistic extrapolation to the desired protection goals (Galic et al, 2010;Larras et al, 2022). Practical applications of population models have focused mainly on plant protection products (Dohmen et al, 2015;Galic et al, 2012;Garber et al, 2022) but examples in a metal context are also available (Janssen et al, 2021;Vlaeminck et al, 2019Vlaeminck et al, , 2020Weighman et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…To implement the IT model, we assumed that the threshold for both adult and juvenile brook trout was reached within 30 days of exposure, which is supported by model fits of Cu toxicity to the related species rainbow trout (Janssen et al, 2021). We implemented the IT model by killing a fixed fraction of randomly selected adults or juveniles after 30 days of exposure, corresponding to the observed relative survival fraction at the end of the test (Supporting Information, Table S1-5).…”
Section: Incorporation Of Cu Toxicity In the Population Modelmentioning
confidence: 99%
“…Because the chosen method of implementation for survival effects (IT or SD) can affect population-level predictions, this led to additional uncertainty in our population-level predictions. In an earlier study, Janssen et al (2021) found that the IT model was the most plausible model to explain Cu mortality to juvenile rainbow trout, based on results obtained with waters that had a wide variety of physicochemical compositions. Because both our present study and that of Janssen et al (2021) are about trout species, one could assume that the NOEC pop values obtained with the IT simulations may be the most realistic ones in our present study.…”
Section: Sd or Itmentioning
confidence: 99%
See 1 more Smart Citation